The macroeconomic effects of different CBDC regimes in an economy with a heterogeneous household sector - Jana Anjali Magin; Ulrike Neyer; Daniel Stempel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
Many central banks discuss the introduction of a Central Bank Digital Currency (CBDC). Empirical evidence suggests that households may differ in their willingness to hold CBDC. Against this background, this paper investigates the macroeconomic effects of different CBDC regimes in a New Keynesian model with a heterogeneous household sector. We consider that a CBDC may facilitate transactions. In particular, households will face additional transaction costs if they do not hold their optimal mix of conventional forms of money and CBDC. We analyze the impact of four different CBDC regimes: (i) no CBDC, (ii) each household may hold an unlimited amount of CBDC, (iii) the central bank sets a maximum amount of CBDC each household is allowed to hold, (iv) the central bank uses the CBDC as a monetary policy instrument by adjusting the maximum amount of CBDC each household is allowed to hold. Generally, we find that the introduction of a CBDC increases economy-wide utility as it allows higher consumption. Moreover, the shock absorption capability increases in an economy with CBDC. This particularly applies to the case when the central bank uses the CBDC as a monetary policy instrument. By adjusting the maximum amount of CBDC, the central bank can stabilize prices more effectively after adverse shocks. However, this stabilization implies distributional effects between households.
Keywords: E52; E42; E58; E41; E51; 330; Central bank digital currency; monetary policy; household heterogeneity; central banks; New Keynesian model